2003
DOI: 10.1007/978-3-540-39867-7_20
|View full text |Cite
|
Sign up to set email alerts
|

EYES – Energy Efficient Sensor Networks

Abstract: Abstract. The EYES project (IST-2001-34734) is a three years European research project on self-organizing and collaborative energy-efficient sensor networks. It will address the convergence of distributed information processing, wireless communications, and mobile computing. The goal of the project is to develop the architecture and the technology which enables the creation of a new generation of sensors that can effectively network together so as to provide a flexible platform for the support of a large varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Each node has communication range of 30m. Power consumption for transmission is set to 24mW and that for reception is set to 14.4mW, as in the EYES sensor prototypes [10]. The sensors that perform a look-up operation and then send a message to the server are uniformly chosen between the deployed sensors.…”
Section: Resultsmentioning
confidence: 99%
“…Each node has communication range of 30m. Power consumption for transmission is set to 24mW and that for reception is set to 14.4mW, as in the EYES sensor prototypes [10]. The sensors that perform a look-up operation and then send a message to the server are uniformly chosen between the deployed sensors.…”
Section: Resultsmentioning
confidence: 99%
“…It can be concluded that time-outs are an effective way to resolve the idle listening issue under variable load of traffic. The implementation of T-MAC has shown energy conservation both in simulation in OMNET++ [55] and on real hardware (EYES nodes) [56]. It is shown that during a high load, nodes communicate without sleeping however, during low traffic load the nodes will use their radios as little as 2.5% of the time, resulting in 96% of energy conservation compared to a traditional MAC protocol.…”
Section: • Expiration Of Periodic Frame • Message Reception • Collisimentioning
confidence: 99%
“…SensorSimulator is developed on the discrete event simulator OMNeT++ 39, mainly intended to support sensor network simulations. The simulator contains a model of the EYES wireless sensor node 40. Furthermore, the simulator has the same limits as the EYES nodes.…”
Section: Performance Analysismentioning
confidence: 99%